A new quantitative reverse phase high-performance liquid chromatographic method for the quantification of Rilpivirine hydrochloride in bulk and dosage form - Sonam Patel, Krishnaveni Nagappan, Gouru Santhosh Reddy (Journal of Applied Pharmaceutical Science, 2018)
Objective: The aim of this present study is to develop a precise, accurate, and linear reverse-phase high-performance liquid chromatographic (RP-HPLC) method for the assessment of Rilpivirine hydrochloride in the pharmaceutical dosage form. Methods: The chromatographic system employs a reverse phase shim-pack C18 column (150 × 4.6 mm; 5 μ) using the mobile phase acetonitrile: ammonium acetate buffer (0.05 M) (pH-3.5 equalized with glacial acetic acid) in the proportion of 60:40 v/v, delivered at a flow rate of 0.8 ml/minutes with the detection wavelength of 291 nm. Results: The developed method resulted in retention of Rilpivirine hydrochloride at 4.5 minutes. Rilpivirine hydrochloride exhibited a linear relationship (r2 > 0.999) over the analytical range of 5–50 μg/ml. The precision is represented by a relative standard deviation of 0.709%. The percentage recovery was observed in the range of 98%–102%, indicating the accuracy of the study. The detection limit and quantification limit were found to be 0.104 and 0.315 μg/ml, respectively. Conclusion: A precise, accurate, rapid, and linear RP-HPLC method has been developed and validated for the quantification of Rilpivirine hydrochloride in bulk and in tablet formulation (25 mg) as per ICH Q2A (R2) guidelines. The developed and validated method can further be used for routine analysis of Rilpivirine hydrochloride in various pharmaceutical industries.
Keywords: Rilpivirine hydrochloride, RP-HPLC, Method optimization, Method validation.